Análise de rendimento industrial da tilápia do Nilo (Oreochromis niloticus, Linnaeus, 1758) - Azevedo, Adriano Vitor (2015)
The objective was proportional an analysis in the processing of Nile tilapia in different weight ranges. A total of 200 tilapias were used, separated into four weight groups: P1 (180 to 220 g); P2 (280-320 g); P3 (380-420 g) and P4 (480-520 g), derived from a farmers association of fish in net-tank from the hydroelectric Governor José Richa-Salto Caxias, Pr. The fish were processed in an industrial environment . For statistical analysis, we used the analysis of variance, followed by F test at 5% significance level, and when significant Tukey test. The found average weights were P1 (206g), P2 (297g); P3 (382g) and P4 (491g). A clean trunk proceeds analysis was significant for P2 weight ranges (51.15%), P3 (51.36%) and P4 (53.01%). Proximate analysis for clean trunks were used, and the weight ranges P3 and P4 were significant for protein and fat. As the production cost and manufacturing proceeds for the clean trunk, the weight range is indicated P2